1992
DOI: 10.1002/jcp.1041520313
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C remains functionally active during TPA induced neuronal differentiation of SH‐SY5Y human neuroblastoma cells

Abstract: SH-SY5Y human neuroblastoma cells can be induced to differentiate into a neuronal phenotype by treatment with 12-O-tetradecanoylphorbol-13-acetate (TPA). In other cell systems, TPA treatment frequently leads to down-regulation of protein kinase C (PKC). However, we now report that TPA-treated and non-treated SH-SY5Y cells express PKC-alpha, but not PKC-beta and PKC-gamma, mRNA. Furthermore, only a slight down-regulation of the PKC-alpha protein could be seen during prolonged treatment with 16 nM TPA, the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
25
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
(30 reference statements)
7
25
0
Order By: Relevance
“…It has been shown that PKCa is the isoform expressed in SH-SY5Y cells, and that this enzyme remains functionally active after long-term treatment with concentrations of TPA that induce neuronal di erentiation. Very high concentrations of TPA appear to be required to cause complete down-regulation of PKCa in SH-SY5Y cells (Parrow et al, 1992) and, in agreement with this observation, preincubation with micromolar concentrations of TPA abrogates activation of the RARb2 promoter by the phorbol ester. PKC is an important point of intersection of di erent signal transduction pathways since many cellular receptors for extracellular chemical messengers can activate PKC (Nishizuka, 1995).…”
Section: Discussionsupporting
confidence: 75%
“…It has been shown that PKCa is the isoform expressed in SH-SY5Y cells, and that this enzyme remains functionally active after long-term treatment with concentrations of TPA that induce neuronal di erentiation. Very high concentrations of TPA appear to be required to cause complete down-regulation of PKCa in SH-SY5Y cells (Parrow et al, 1992) and, in agreement with this observation, preincubation with micromolar concentrations of TPA abrogates activation of the RARb2 promoter by the phorbol ester. PKC is an important point of intersection of di erent signal transduction pathways since many cellular receptors for extracellular chemical messengers can activate PKC (Nishizuka, 1995).…”
Section: Discussionsupporting
confidence: 75%
“…SH-SY5Y cells express at least PKC-␣, PKC-⑀, and PKC- (21). A sustained PKC activity, measured as phosphorylation of myristoylated alanine-rich protein kinase C substrate (MARCKS), is detected during differentiation of SH-SY5Y cells (22), and treatment with a high concentration of TPA (1.6 M) that down-regulates PKC-␣ completely only induces poor differentiation (21,23,24). Furthermore, inhibition of PKC activity by specific inhibitors blocks differentiation induced by 16 nM TPA in FCS or the combination of bFGF and IGF-I with respect to both morphological and transcriptional events (24).…”
Section: P130mentioning
confidence: 99%
“…Therefore, the initial phosphorylation of p130 cas seemed not to be strictly correlated to activation of a differentiation program. Since the differentiation protocols studied, as well as the stimulation by phorbol esters, IGF-I, and bFGF, all result in the activation of PKC (14,22), the detected increase in tyrosine phosphorylation of p130…”
Section: Pkc-dependent P130mentioning
confidence: 99%
“…In addition, differentiated SH-SY5Y cells become functional as they accumulate norepinephrine in dense core granules and build up an action potential, which is depolarized by acetylcholine, resulting in release of stored neurotransmitters (1). Protein kinase C (PKC) isoforms have been suggested to regulate TPA-mediated neuroblastoma cell differentiation (2). However, PKC family consists of at least 12 members, and each one of them has distinct biological functions.…”
mentioning
confidence: 99%